Management accounting : problems and solutions - Hingorani, N. L.; Ramanathan, A. R. (New Delhi : Sultan Chand & Sons, 1985)
This self-teaching guide first explains how and why management accounting is at the intersection of accounting information and decision-making. This book is written to take the mystery out of management; it provides the major accounting concepts and procedure in a concise form. Then, you get details on cost allocation systems, cost analysis, profit planning, operational budgeting, performance evaluations, and more. Featuring end of chapter quizzes and a final exam, this book will teach you the in and out of management accounting in no time at all.
ucj 18/01/2019
Loans
Keywords: Managerial accounting; Performance evaluation